O dom do Espírito Santo em Atos 2,1-13: uma análise pragmalinguistica e intertextual - Silva, João Claudio Rufino Rodrigues (2024)
The thesis aims to elucidate Luke's communicative strategy in the account of the descent of the Holy Spirit at Pentecost, using methods of linguistic pragmatics and intertextual analysis. It is justified by the need to understand the theological implications and doctrinal disputes arising from this narrative throughout the history of Christian exegesis. The central hypothesis is that Luke, inserted in 1st century Judaism, uses the language of the time to position the primitive Christian community in continuity with biblical Israel. Theoretically, the thesis is based on concepts of linguistic pragmatics, applying speech act theory and intertextual analysis to biblical exegesis. The results obtained demonstrate that Luke's narrative in Acts 21-13 is a complex communicative event, which establishes a dialogue between God and humanity, with profound eschatological and theological implications